Pengaruh Akuntabilitas Auditor, Independensi Auditor, Dan Profesionalisme Auditor Terhadap Kualitas Audit - Lailatus Sangadah (Politeknik Ganesha Medan, 2022)
This study aims to examine the effect of auditor accountability, auditor independence, and profesionalisme on audit quality. This research is a quantitative research using primary data questionnaire.The participants of this study were auditors who worked at the Yogyakarta Public Accounting firm. The sampling technique in this study used convenience sampling. The analytical method to test the data i this study used multiple regression analysis using SPSS 20 software.The result of this study indicate that auditor accountability, auditor independence and profesionalism have a significant effect on audit quality.